Swallow This: Childhood and Adolescent Exposure to Fast Food Restaurants, BMI, and Cognitive Ability - Sara Abrahamsson; Aline Bütikofer; Krzysztof Karbownik (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using spatial and temporal variation in openings of fast food restaurants in Norway between 1980 and 2007, we study the effects of changes in the supply of high caloric nutrition on the health and cognitive ability of young adult males. Our results indicate that exposure to these establishments during childhood and adolescence increases BMI and has negative effects on cognition. Heterogeneity analysis does not reveal meaningful differences in the effects across groups, including for those with adverse prenatal health or high paternal BMI, an exception being that cognition is only affected by exposure at ages 0-12 and this effect is mediated by paternal education.
Keywords: I12; I20; J13; L66; 330; fast food restaurants; food supply; BMI; obesity; cognitive ability